Study on the characteristic of the grounding fault on the cascaded midpoint side of the hybrid cascaded HVDC system - Ren, Yonghao; Sun, Huadong; Wang, Shanshan; Zhao, Bing; Xu, Shiyun; Liu, Min; Lian, Panjie (Frontiers in Energy Research, 2023)
A novel approach to HVDC transmission, the hybrid cascaded HVDC system combines the MMC's robust system support capabilities with the LCC's advantage of high power transmission capacity. Meanwhile, the HVDC system is among the key elements of the smart grid where the artificial intelligence are widely applied. However, the characteristic of the grounding fault on the cascaded midpoint side of the hybrid cascaded HVDC system is still unclear. This paper analyzes the fault characteristics using analytic methods and the impact of the fault. Firstly, the topology and basic control strategy is submitted. Then, the fault response process is analyzed by dividing into two parts: the MMCs and LCC at the inverter side. The theoretical analysis is also carried out separately. Meanwhile, the impact of the fault on the HVDC system and the AC network is analyzed. So even after the HVDC system is disabled, the AC network can still supply fault current to it using an anti-parallel diode. The simulation results shows that the analysis method proposed in this paper is feasible and the theoretical analysis is correct. The method proposed in this paper can provide a theoretical basis for equipment selection of HVDC system and smart grid construction.